Air Pollution Exposure Duration and Its Correlation with Triglyceride, HDL, and Atherogenic Index in Online Motorcycle Drivers - Adrian Stefanus Herawan; Edward Kurnia Setiawan Limijadi; Donna Hermawati; Lusiana Batubara (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2022)
Background: The most restoration material used currently in dentistry was composite resin. The newest generation of composite resin was bulk-fill composite resin. The bulk-fill composite resin had advantages of lower polymerization contraction and a more straightforward and faster restoration technique. One of the factors which could affect the hardness of composite resin was the consumption of acidic drinks. The acidic beverage that people often consumed is coffee. A few coffee brewing methods were espresso and drip brewing.Objective: This research aimed to identify the effects of coffee soaking through espresso and drip brewing methods on bulk-fill composite resin's hardness.Methods: his research was experimental research, with a post-test control group design and a total sample of 27 samples. The soaking process was taken for seven days at a temperature of 37˚C on artificial saliva, espresso, and drip brewing coffee methods. The hardness of bulk-fill composite resin was measured after seven days by using Vickers hardness. The statistic test exerted One-Way ANOVA.Results: This research found a significant difference in bulk-fill composite resin's hardness among all groups, p-value = 0.00 (p<0.05). The result of the post-hoc LSD test showed a significant difference in the change of bulk-fill composite resin hardness between the artificial saliva group and espresso group (p=0,00) and no significant difference found between the artificial saliva group and drip brewing group (p=0.85).Conclusion: Soaking with espresso coffee has the smallest hardness value compared to soaking with drip brewing coffee and artificial saliva, so soaking with espresso coffee is the most influential on the hardness of the bulk fill composite resin.